Objective characteristic parameters of loudspeakers in the aspect of psychoacoustic data - HOJAN, E. (Archives of Acoustics, 1991)
The paper presents the proposal of an objective evaluation of loudspeakers. Certain subjective properties of the hearing organ should be taken into consideration. The aim of these loudspeaker investigations is to correlate results of objective investigations with a subjective evaluation of the sound emitted by loudspeakers.